2015
DOI: 10.1039/c5ce00659g
|View full text |Cite
|
Sign up to set email alerts
|

Controlling alloy formation and optical properties by galvanic replacement of sub-20 nm silver nanoparticles in organic media

Abstract: Galvanic replacement is a versatile synthetic strategy for the synthesis of alloy and hollow nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…In 2015, based on Xia's and Sastry's previous studies, [39,40] Holmes and co-workers reported that Au atoms replaced Ag atoms of multiply twinned AgNPs to form nanorings, nanocages, or solid alloy NPs depending on the size of the NPs. [41] From these results, 8 nm AgNPs favor nanorings, while smaller AgNPs (6 nm) form solid alloys, and larger AgNPs (15 nm) lead to nanocages (Figure 5).…”
Section: Nanoringsmentioning
confidence: 90%
See 2 more Smart Citations
“…In 2015, based on Xia's and Sastry's previous studies, [39,40] Holmes and co-workers reported that Au atoms replaced Ag atoms of multiply twinned AgNPs to form nanorings, nanocages, or solid alloy NPs depending on the size of the NPs. [41] From these results, 8 nm AgNPs favor nanorings, while smaller AgNPs (6 nm) form solid alloys, and larger AgNPs (15 nm) lead to nanocages (Figure 5).…”
Section: Nanoringsmentioning
confidence: 90%
“…Reproduced with permission [41]. c,f,i) HRTEM of AgAu nanocages (c), nanorings (f), and solid alloyed NPs (i).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ability to perform nonaqueous galvanic replacement of Ag NP templates of various sizes and shapes, with control over the stoichiometry of the final product, has important implications for LSPR tuning and surface functionalization. Reports of nonaqueous galvanic replacement approaches, which exist only for toluene, dichlorobenzene, and chloroform, all focus on the replacement of sub‐25 nm isotropic Ag templates with Au to produce Au nanocages; as of yet none involve large, anisotropic structures or tunable morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some drawbacks to conventional galvanic replacement. First, excessive replacement causes fragmentation or aggregation because of uncontrollable replacement after the formation of a nanoshell [104,105]. Second, insoluble byproducts such as AgCl are formed by the dissolved template element (Ag + ), and the counter ion of the replacing cation (Cl -) is deposited on the surface of the particles, reducing colloidal stability [106][107][108].…”
mentioning
confidence: 99%